A BAFF Receptor His159Tyr Mutation in Sjögren's Syndrome–Related Lymphoproliferation. Issue 10 (23rd September 2015) - Papageorgiou, Aristea; Mavragani, Clio P.; Nezos, Andrianos; Zintzaras, Elias; Quartuccio, Luca; De Vita, Salvatore; Koutsilieris, Michael; Tzioufas, Athanasios G.; Moutsopoulos, Haralampos M.; Voulgarelis, Michael
Abstract : Objective: To study the prevalence, clinical associations, and functional implications of the His159Tyr mutation of the BAFF receptor (BAFF‐R) in patients with Sjögren's syndrome (SS). Methods: The BAFF‐R His159Tyr mutation was evaluated using polymerase chain reaction (PCR)–based assays in 247 patients with SS (of whom 70 had SS complicated by lymphoma [SS‐lymphoma]), 145 with systemic lupus erythematosus (SLE), and 101 with rheumatoid arthritis (RA), as well as 180 healthy controls. Real‐time PCR and Western blotting were performed for the quantification of both NF‐κB1 and NF‐κB2 messenger RNA (mRNA) transcript and protein levels in isolated B cells from patients with SS‐lymphoma carrying the mutation (SS‐lymphoma–BAFF‐RHis159Tyr –derived B cells) compared to B cells from patients with SS‐lymphoma who were not carriers of the mutation and healthy controls. Results: Both the SS‐lymphoma and SS‐nonlymphoma patient subgroups exhibited significantly higher frequencies of the His159Tyr BAFF‐R mutation compared to healthy controls (8.6% of SS‐lymphoma patients and 6.2% of SS‐nonlymphoma patients versus 1.7% of healthy controls; P = 0.02 and P = 0.04, respectively). The corresponding frequencies of the His159Tyr BAFF‐R mutation in SLE and RA patients were 3.5% and 3%, respectively. Of interest, 71.4% of the SS patients with mucosa‐associated lymphoid tissue (MALT) lymphoma who were between the ages of 31 and 40 years at disease onset were mutation carriers. The generalized odds ratio for the development of SS‐related MALT lymphoma in the younger age at onset (age <40 years) group in the presence of the BAFF‐R mutation was 6.1 (95% confidence interval 2.0–18.7) ( P < 0.01). Expression of NF‐κB at both the mRNA and protein level was up‐regulated in SS‐lymphoma–BAFF‐RHis159Tyr –derived B cells. Conclusion: This study identifies an increased prevalence of the BAFF‐R His159Tyr mutation in patients with SS, particularly in those with SS complicated by MALT lymphoma whose disease onset occurred at a younger age. BAFF‐RHis159Tyr –mediated activation of the alternate NF‐κB pathway might contribute to the pathogenesis of SS‐related lymphoproliferative disease.